Pengaruh Dimensi Mutu Pelayanan dan Indikator Perilaku Pasien terhadap Minat Kunjungan Ulang Rawat Inap di Puskesmas Kusuma Bangsa - Nia Dewi Amina; Suwondo Suwondo; Teguh Irawan (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
This research is motivated by a decrease in the value of IKM in 2022 which has an impact on decreasing interest in repeat visits in 2023 related to the dimensions of service quality and patient behavior indicators. There are patient complaints such as doctors not being there when patients need and difficulty getting referrals. The purpose of this study was to analyze the effect of service quality dimensions and patient behavior indicators on interest in inpatient re-visits at Kusuma Bangsa Health Center. This study uses quantitative methods. Data collection by interview using a questionnaire. Respondents in this study totaled 103 patients. Data analysis using logistic regression test. The results showed that patients who were interested in making a repeat visit (55.3%), patients categorized both the quality dimension (68%) and the patient behavior indicator (53%). There is a significant influence between interest in repeat visits with patient behavior indicators with a p value of 0.010. Kusuma Bangsa Health Center is expected to prioritize improving access to services and including doctors to be on duty 24 hours.